Factores de riesgo asociados a retinopatía diabética en diabetes mellitus tipo 2 - Rosillo-Flores, Esther (2004)
Objective. To determine the prevalence of diabetic retinopathy and its association to factors of risk like hypertension, dyslipidemia, obesity, age and duration of the diabetes. Material and methods: It was carried out a prospective, observational and analytic study in the Instituto Nacional de Oftalmología of Lima, from August 1 2000 to January 30 2001. The state retinal was evaluated by means of the exam of bottom of eye previous glycemia compensation. The patients were randomized in two groups: patients with retinopathy and without retinopathy. The samples of blood and urinates they were taken to determine glycemia, HbA1c glycosidic, profile lipidic, urea, creatinine, creatinine purification and proteinuria. Results. It was studied 97 cases, 45 males and 52 women, and it was observed that the prevalence of ophthalmologic retinopathy in patients diabetic type 2 were it was 58,8% (53% males and 47% women). The type more frequent retinopathy was the proliferative diabetic retinopathy (59,6%). It was found that the biggest prevalence in diabetic retinopathy was related with the overweight and the obesity (P < 0,05), dyslipidemia (P < 0,05) and PAS 120 mmHg. (OR: 2,29; RR: 1,043; p < 0,05) and PAD 95 mmHg (OR: 3,96; RR: 2,88; P < 0,05). The treatment with photocoagulationwas carried out in 39% of cases. Conclusions: It was demonstratedthat the hyperglycemia, obesity, dyslipidemia, arterial hypertension are factors of risk for diabetic retinopathy (p < 0,05).